Field notes contributed by Dale Stone, spring 1992 - Stone, Daleet al (1992)
List of birds and locations contributed by Dale Stone. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1992. Plustek - flatbed